A tornászat, avagy a gimnasztika államosítása (Szociológiai Szemle, 2024)
Miklós Hadas’ text is an excerpt from a book entitled Sports and Masculinity he is currently working on. His starting question is the following: What explains that in the 20th century Hungary becam e a “great sports power”? The answer is attempted through the study of social dispositions, i.e. historically conditioned gendered behavioral patterns of different social groups. It is argued that in the past two centuries of modernity, masculine passions have been channeled intő new directions, aggressive fight aimed at destroying the enemy being replaced by civilized com petition. In the present text the process is analyzed during which gym nastics, the independent pre-sport of the emerging Hungarian bourgeoisie, is transformed into com pulsory physical training in Hungarian state-schools after 1867. Germán and Swedish type physical trainings are confronted and the strategies of different fractions (exclusion/inclusion/expansion) are also dealt with.